Tear film thickness and stability following femtosecond-assisted laser in situ keratomileusis: a comparison of high- and low-myopia - Li, Yan; Yan, Haibo; Yang, Hua; Niu, Shiyang; Qi, Hong; Zhang, Chunyan (Frontiers in Medicine, 2025)
BackgroundTo investigate the relationship between tear film thickness, corneal epithelial thickness, tear film breakup location, and dry eye in patients with high- and low-myopia undergoing femtosecond-assisted laser in situ keratomileusis (FS-LASIK).MethodsA total of 52 patients (52 eyes) were enrolled and divided into a low-myopia group (LMG; spherical equivalent ≤−3.00 D; 26 eyes) and a high-myopia group (HMG; spherical equivalent ≥−6.00 D; 26 eyes). The Ocular Surface Disease Index (OSDI), fluorescein tear film breakup time (FBUT), corneal epithelial thickness (CET), tear film thickness (TFT), and other tear film stability markers were evaluated preoperatively. Each parameter was evaluated preoperatively at 1 and 3 months postoperatively.ResultsAt 1 month postoperatively, the HMG showed significantly higher OSDI scores and CET compared to the LMG (p < 0.05). Conversely, the FBUT and TFT were significantly lower in the HMG at the same time point (p < 0.05). Within a 6- to 7-mm corneal diameter, the TFT was significantly lower in the HMG than in the LMG (p < 0.05). Furthermore, the change in CET from baseline at 1 and 3 months postoperatively was significantly greater in the HMG, especially within the 5-mm corneal diameter (p < 0.05). There were no significant differences in spherical equivalent (SE) or uncorrected distance visual acuity (UDVA) between 1 and 3 months postoperatively within either group (p > 0.05).ConclusionThe observed alterations in tear film thickness, tear film distribution, FBUT, and tear film breakup location, affected by varying corneal stromal ablation depths, contribute to the development of dry eye disease following FS-LASIK. The extent of corneal epithelial remodeling after FS-LASIK correlates with the degree of refractive correction but not with refractive regression, and may play a role in tear film stability recovery.